(untitled) (mathematica didactica, 2023)
Closing subject-related conceptual learning gaps is a central goal of supporting children with mathematical learning difficulties. Therefore, current research in the field of mathematics education tries to identify conditions for success to support these children in catching up conceptual understanding. The study presented in this paper focuses on a language-responsive support with a focus on relating different mathematical representation at the beginning of the second grade of primary school. The results show that mathematics teaching based on these design principles significantly supports children in developing conceptual understanding of number and addition.